2003
DOI: 10.1210/me.2002-0120
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acids Induce the Expression of the Human Peroxisome Proliferator-Activated Receptor α Gene via Activation of the Farnesoid X Receptor

Abstract: Peroxisome proliferator-activated receptor alpha (PPARalpha) is a nuclear receptor that controls lipid and glucose metabolism and exerts antiinflammatory activities. PPARalpha is also reported to influence bile acid formation and bile composition. Farnesoid X receptor (FXR) is a bile acid-activated nuclear receptor that mediates the effects of bile acids on gene expression and plays a major role in bile acid and possibly also in lipid metabolism. Thus, both PPARalpha and FXR appear to act on common metabolic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
241
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 414 publications
(253 citation statements)
references
References 68 publications
9
241
1
2
Order By: Relevance
“…It is widely known that an increase of triglyceride synthesis in liver plays an important role in NAFLD models [14,[21][22][23]. In rodents, an increase in the amount of synthesized lipids was observed in liver and adipose tissue cells, while in humans, it was primarily in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that an increase of triglyceride synthesis in liver plays an important role in NAFLD models [14,[21][22][23]. In rodents, an increase in the amount of synthesized lipids was observed in liver and adipose tissue cells, while in humans, it was primarily in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…39 Recent investigation indicated that the nuclear farnesoid x receptor and oxysterol x receptor bind bile acids, resulting in a positive/negative regulation in the transcription of several gene products. [40][41][42][43][44] However, there is no binding site for these nuclear receptors in the human PLA 2 IIA gene promoter. 39 In addition, UDCA has been reported to have a limited affinity for these nuclear receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture medium containing retrovirus was collected 48 h after transfection. For cell transduction, 2 ml of viral stock and 8 ml of fresh Dulbecco's modified Eagle's medium were mixed and added in a 100-mm dish of 0.5 ϫ 10 6 BOECs with 8 g/ml Polybrene. Transduction efficiency using this approach was uniformly Ͼ90%.…”
mentioning
confidence: 99%